Antibody Response of Non-Dewormed and Dewormed Village Chickens to Sheep Red Blood Cells - Saasa , Ngonda; Siwila, Joyce; M`kandawire, Ethel; Nalubamb, King Shimumbo (International Journal of Poultry Science, 2014)
The economic activities of rural communities rely on small scale enterprises such as raising village chickens. However, the impact of many infectious diseases has hampered the activities of these rural communities necessitating the use of vaccines to control and mitigate the negative effects of the diseases. Understanding the effect of helminths on the immune system and ultimately on the outcome of vaccinations is important. In this study, the effect of deworming on the immune response was evaluated by antibody titres to sheep red blood cells using direct hemagglutination in 41 naturally helminth-infested village chickens. We found that the immune response of both the control and dewormed groups of chickens, respectively, to sheep red blood cells were similar at primary (mean titres 726.74 and 819.58; p = 0.78) and secondary (mean titres 1822.24 and 1792.92; p = 0.95) levels. The results show that helminth infestation of clinically healthy chickens may not grossly affect the immune response of village chickens, suggesting that naturally infested chickens can be immunized without deworming.